Предмет: Алгебра, автор: anna890890

83 номер, пожалуйста

Приложения:

Ответы

Автор ответа: NNNLLL54
1

(2x^2-x+1)^2+6x=1+9x^2\\\\(2x^2-x+1)^2=9x^2-6x+1\\\\(2x^2-x+1)^2=(3x-1)^2\\\\(2x^2-x+1)^2-(3x-1)^2=0\; \; \; \; \; \; [\; A^2-B^2=(A-B)(A+B)\; ]\\\\(2x^2-x+1-3x+1)(2x^2-x+1+3x-1)=0\\\\(2x^2-4x+2)(2x^2+2x)=0\\\\2\cdot 2x\cdot (x^2-2x+1)(x+1)=0\\\\4x\cdot (x-1)^2\cdot (x+1)=0\\\\x_1=0\; ,\\\\x-1=0\; ,\; \; x_2=1\\\\x+1=0\; ,\; \; x_3=-1\\\\Otvet:\; \; x_1=0\; ,\; x_2=1\; ,\; x_3=-1\; .

Автор ответа: kseniaiap5y74u
0

ответ х=1, х=0, х=-1

Приложения:
Похожие вопросы
Предмет: Английский язык, автор: bogdanzeman11